Analysis of customer lifetime value: Development of alternative models - Ekinci, Yeliz (Institute of Science And Technology, 2011)
The general aim of this study is to develop a model to provide a guide to the future marketing decisions of a firm, using predicted customer lifetime values. Developed as such, it can be applied in a specific industry. In this thesis, the banking industry is selected for real life application of the proposed model. The proposed framework for the prediction of customer lifetime value tries to eliminate the limitations and drawbacks of the majority of models encountered in the literature through a simple and industry-specific model which has easily measurable and objective indicators. In addition, this model predicts the potential value of the current customers rather than measuring the current value which is generally used in the majority of previous studies. This study makes a contribution to the literature by helping to make future marketing decisions via Markov Decision Processes for a company that offers several types of products. Another contribution is that the states for Markov Decision Processes are also generated using the predicted customer lifetime values of the customers. Finally, the real world application of the proposed model is another important contribution to the literature because the applicability of the previous studies is often a subject of concern. Therefore, it is thought that the proposed framework and the developed model can guide both practitioners and researchers.

Bu çalışmanın ana amacı potansiyel müşteri yaşamboyu değeri tahminine dayanarak, geleceğe yönelik optimal pazarlama promosyon kararı veren ve belirli bir sektöre özel (bankacılık) basit, uygulanabilir bir model geliştirmektir. Çalışmada önerilen müşteri yaşamboyu değeri ölçüm modeli, kolay ve sektöre özel bir modelle, nesnel değişkenler kullanarak literatürdeki eksiklikleri bertaraf etmeye çalışmıştır. Literatürdeki pek çok modelin aksine, mevcut müşteri yaşamboyu değerini değil, geleceğe yönelik potansiyel değeri tahmin etmektedir. Çalışma, birden fazla çeşit ürün/hizmet sunan bir firma (banka) için potansiyel müşteri yaşamboyu değeri tahminine dayanarak, Markov karar süreçleri kullanarak geleceğe yönelik optimal pazarlama promosyon kararı veren, ve literatürde ilk olan bir model geliştirmektedir. Çalışmanın diğer bir katkısı da, Markov karar süreçleri için gerekli olan müşteri bölümlendirmeyi yine müşterinin potansiyel müşteri yaşamboyu değerlerine göre yapmasıdır. Geçmiş çalışmalarda önerilen modellerin pek çoğunda, gerçek veriyle doğrulama bulunmaması göz önüne alındığında, bu çalışmanın önerdiği modeli gerçek veriyle de desteklemesi literatüre sağlanan diğer bir katkıdır. Bu nedenlerle, önerilen çerçevenin ve elde edilen bulguların, hem uzmanlar hem de araştırmacılar açısından değerli bir araç olacağı düşünülmektedir.
Müşteri yaşamboyu değeri analizi: Alternatif modeller geliştirilmesi
Theses (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2011
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2011
Keywords: Markov decision processes , Optimization, Marketing, Data mining; Markov karar süreçleri , Optimizasyon , Pazarlama , Veri madenciliği